PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK DENGAN PENDEKATAN SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY (SETS) PADA POKOK BAHASAN HIDROLISIS GARAM KELAS XI SMA - Yuni Permata Sari; Rini '; Rasmiwetti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: Abstract : The student activities sheet based on Science, Environment, Technology and Society (SETS) for chemistry grade XI senior high school in hidrolize of salt materials has been developed. Method of this research is Research and Development (R & D). The instruments of this research are questioners which are given to the validators. There are three validators, one of validators is lecturer in chemistry university of riau and two validators are teachers of Babussalam senior high school, Pekanbaru. The result of this research shows the validity of student participant exercise sheet is 90,65 %, and category of validity is very high. Based on the result analysis can be concluded that the learning device consist of student activities sheet based on Science, Environment, Technology and Society (SETS) for chemistry grade XI senior high school in hidrolize of salt materials has been valid and proper.Keywords: Student participant exercise sheet, learning process envisioned Science, Environment, Technology and Society (SETS), R&D, hidrolize of salt